THE ROLE OF INSTANT MESSANGING ON THE EFFECTIVENESS OF LECTURER'S PERFORMANCE AT THE UNIVERSITAS ABDURRAB - Hartati, Seri; Arisandi, Diki (PEOPLE: International Journal of Social Sciences, 2017)
Recently education has a high demand in terms of communication services, instant messaging (IM) becomes an option in communicating in University as the service increases in accordance with user needs. Previous works have suggested that the use of IM may disrupt the working activities. But in recent years research shown that IM utilization had increased in work life. By using IM technology allows the information shared quickly, precisely and accurately, so that surely will improve the effectiveness of work. Lecturers are the critical aspectto make a better improvement of the university its self. With the development of communication technology will impact the emergence of various types of activities based on technology, all of which are based on electronics such as instant messaging which will help the effectiveness of lecturer's performance. This research uses quantitative method to measure the significance of the effect of instant messaging on the performance of lecturers at the Universitas Abdurrab. This research shown that all lecturers using instant messaging in their work have a significant influence on their performance. Through this research is expected to contribute to encourage efforts to increase the use of Instant Messaging, so that the Internet Service Providers can provide more specific services for the education, especially in the university to support the establishment of e-education and e-management.